TINJAUAN YURIDIS TERHADAP PERLINDUNGAN HUKUM OLEH INTERNATIONAL LABOUR ORGANIZATION (ILO) KEPADA PEKERJA/BURUH PEREMPUAN DAN ANAK DI INDONESIA - Theddy Theddy; Ningrum Natasya Sirait; Jelly Leviza (Journal of USU International Law, 2019)
A JURIDICAL VIEW REGARDING THE LEGAL PROTECTIONS TO WOMEN AND CHILD’S LABOURS BY INTERNATIONAL LABOUR ORGANIZATION (ILO) IN INDONESIA *) Prof. Dr. Ningrum Natasya Sirait, S.H., M.LI. **) Dr. Jelly Leviza, S.H., M.Hum. ***) Theddy ABSTRACT Labours must have legal protections. Legal protections are given by states by national law, and international organization by International Labour Organization (ILO) with conventions and recommendations. Women and Child’s labours always being discriminated in every aspects of work, harm, and never have the rights as labours The methods of this research are the study of literature through inventory of materials from books, journals, internet, and other researches. Other materials come from international treaties such as, ILO conventions and recommendations, and Indonesia’s national laws related to the legal protection of women and child’s labour. The research shows that legal protections given by Indonesia and ILO have some relations. Indonesia as the member states of ILO have ratified conventions that give the fundamental rights to labours. Legal protections from the national law could directly achieve by women and child’s labours. ILO has essential acts, such as making conventions, recommendations, monitoring, joint between states, also tripartism and social dialogue. Tripartism is a mechamism where labours, employers, and governments meet each other. All of these are to achieve international labour standards and giving the legal protections to women and child’s labour in Indonesia. Keywords: International Labour Organization, legal protection, women and child’s labour *) Advisor I **) Advisor II ***) Student at Faculty of Law USU